Les familles, l'école et le quechua. Vers une nouvelle réception de l'éducation interculturelle bilingue dans les Andes péruviennes ? - Raphaël Colliaux (Les éditions de la Maison des sciences de l'Homme, 2016)
For twenty years in Peru, reform of Intercultural Bilingual Education (IEB) tries to integrate native languages in classrooms, in addition to Spanish. Long indeed, the school has been instrumentalized to impose Spanish as the dominant language, and to reproduce the authority of urban and literate elites. From a field research conducted in three bilingual schools (Quechua and Spanish) of the department of Cuzco (Andean region), this study see what extent the reform have affected expectations and school practices of families. The evolution allows us to understand better the role that these indigenous peoples attribute themselves on the social and political space.